A Meta-Analysis of Dropout and Metabolic Effects of Antipsychotics in Anorexia Nervosa - Kan, Carol; Eid, Laura; Treasure, Janet; Himmerich, Hubertus (Frontiers in Psychiatry, 2020)
Background Second-generation antipsychotics are often used off-label in the treatment of anorexia nervosa across the clinical spectrum. Patients with anorexia nervosa often cite concerns about metabolic effects, such as weight gain, as reasons for their reluctance to start or continue second-generation antipsychotics. Improving our understanding of the metabolic effect patients experience and reasons underlying their disinclination will enable us to build rapport and guide our clinical decisions. We therefore aimed to conduct a comprehensive review of dropouts, metabolic effects and patient-reported outcomes associated with second-generation antipsychotic in people with AN. Method EMBASE, Medline, and PsycINFO were searched for all relevant studies published until 2019, and retrieved studies were assessed for eligibility as per predefined inclusion criteria. A random-effects meta-analyses was conducted to assess overall dropout rates. Results Of 983 citations retrieved, 35 studies met the inclusion criteria, and 10 studies had appropriate data for meta-analysis. Using the random effects model, the pooled dropout rate in the intervention arm (95% confidence interval) from psychopharmacological trials was 28% (19% to 38%) in people with anorexia nervosa. Personal reasons or factors associated with study were commonest reason for dropout, not adverse events or metabolic effects as hypothesised. Conclusion Compared to personal reasons, drug-related factors such as side effects seem to play a lesser role for the discontinuation of antipsychotic treatment under trial conditions. This suggests an urgent need to consider and fully examine potential individual and patient-related factors that influence dropout rates in psychopharmacological trials and treatment compliance in clinical settings.